2021
DOI: 10.3390/en14020417
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pilot Injection on Combustion and Emission Characteristics of a Low-Speed Two-Stroke Marine Diesel Engine

Abstract: Low-speed two-stroke marine diesel engines dominate the modern global long-distance transportation market; with the increasingly stringent regulations, the combustion and emissions of these engines is gaining intense interest. The primary objective of the present study was to understand the effects of air-fuel mixing by pilot injection strategy on the combustion and emission characteristics of the marine diesel engines through a numerical study. Specifically, a computational fluid dynamic (CFD) model was estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 48 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…MAN ES, despite the shortcomings of ammonia’s ignition and combustion characteristics, has a slow speed and large volume in marine engines, so it can afford time for combustion and can be designed with less heat loss, improving the combustion characteristics of ammonia . Previous studies have shown that micropilot fuel injection timing should be optimized to improve efficiency and combustion stability and reduce exhaust emissions. , In particular, Henke et al reported that spray formation due to changes in micropilot fuel injection timing in a dual-fuel engine greatly affects ignition delay and combustion of low-reactivity fuel …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MAN ES, despite the shortcomings of ammonia’s ignition and combustion characteristics, has a slow speed and large volume in marine engines, so it can afford time for combustion and can be designed with less heat loss, improving the combustion characteristics of ammonia . Previous studies have shown that micropilot fuel injection timing should be optimized to improve efficiency and combustion stability and reduce exhaust emissions. , In particular, Henke et al reported that spray formation due to changes in micropilot fuel injection timing in a dual-fuel engine greatly affects ignition delay and combustion of low-reactivity fuel …”
Section: Introductionmentioning
confidence: 99%
“…18 Previous studies have shown that micropilot fuel injection timing should be optimized to improve efficiency and combustion stability and reduce exhaust emissions. 19,20 In particular, Henke et al 21 reported that spray formation due to changes in micropilot fuel injection timing in a dual-fuel engine greatly affects ignition delay and combustion of low-reactivity fuel. 22 From previous research results, the authors confirmed that to complement the combustion characteristics of ammonia, it is necessary to control the pilot fuel that helps ignite ammonia and that the injection timing and amount of pilot fuel must be optimized according to operating conditions.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that by adjusting the fuel quantity in both pilot injections, it is possible to reduce the NOx and soot emissions. Liang et al [17], analysed the mixing process and its influence on the combustion and emission characteristics under the pilot injection strategy and utilizing a low-speed two-stroke diesel engine, and they also found that, adjusting the pilot injection's time, it is possible to reduce part of the NOx emissions.…”
Section: Introductionmentioning
confidence: 99%